Analysis and Application Review of User Behavior Trajectory Based on the Location Information - Kang Chen; Xiaoyu Huang; Aibao Wang; Caixia Tao; Yinghui Guan; Lei Li (Dianxin kexue)
With the rapid development of spatial data collection technology in recent years，many efforts have been devoted to the research on trajectory based user behavior analysis and its applications，due to their academic interests；they also show promising business opportunities.From the application aspect，in principle，current issues in trajectory based user behavior analysis can be classified into two major categories：the intelligent transportation applications and the user behavior based applications.The state-of-the-art progress of these categories were reviewed.For each category，its main focus and related achievements were discussed.What’s more，the main technical characteristics of the means used were also summarized in current studies.